DISPOSAL OF THE LIFE AS A COMPONENT OF THE RIGHT TO LIFE - Malyarchuk, Nazar V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The paper investigates some of the problems of legal regulation of the constitutional right to life, but the last is viewed not only as a form of biological existence, but also as a way of self-identity in the context of the possibility to dispose of own life. Based on the analysis suggested the possibility of introducing the right to voluntary euthanasia, as a manifestation of the right to life.